Veldaangeleenthede en beweging van wild in die Kalahari - Gemsbokpark - J. J. Morris (Koedoe: African Protected Area Conservation and Science, 1958)
Veldaangeleenthede en beweging van wild in die Kalahari - Gemsbokpark